The Influence of Human Resource Practices and Leadership Style on Job Satisfaction and Cyberdeviance Amongst Administrative Employees in Jordanian Universities - Al-Shuaibi, Ahmad Said Ibrahim (2013)
The advent of the Internet has transformed the way in which people work and live. While the Internet has offered many advantages and benefits to the workplace particularly in terms of speeding up information search, it also has potential drawbacks. One drawback is that people can misuse the Internet while at work. This phenomenon, which is called cyberdeviance, is a form of production deviance. As our theoretical understanding of cyberdeviance is still limited, this study attempts to investigate the role of HR practices and leadership style in cyberdeviant activities. It also seeks to examine the mediating influence of job satisfaction , with the application of social exchange theory. A survey of 273 administrative employees in in four universities in Amman, Jordan who were randomly selected using a cluster technique, was carried out for the period of five months from February until June 2011. Frequency, descriptive statistics, correlation, multiple regression, and hierarchical regression analyses were run to test the research hypotheses. Factor analyses revealed four dimensions of HR practices, i.e., performance appraisal, compensation practice, career advancement, and employment security. Leadership style produced a single dimension labelled supportive leadership style, while job satisfaction yielded two dimensions, namely, satisfaction with pay, and satisfaction with workload. Results showed that performance appraisal and leadership style were significantly and negatively related to cyberdeviance, contrary to expectation. But collectively, the predictor variables of dimensions of HR practices and leadership were found to explain 63.8% of variance in cyberdeviance. Two dimensions of job satisfaction, satisfaction with pay and satisfaction with workload, partially mediated the link between leadership style and cyberdeviance. But satisfaction with pay was found to partially mediate performance appraisal and cyberdeviance. lt is recommended that organizations implement a good performance appraisal system and demonstrate supportive leadership as ways to reduce cyberdeviance at work.